Implementación de un sistema contable por órdenes de producción en la imprenta Offset Print Arts, de la provincia Santo Domingo de los Tsáchilas periodo enero a marzo del 2013 - Mera Macías, Luis Alberto (2014)
The present research work entitled " IMPLEMENTATION OF A SYSTEM FOR ORDERS PRODUCTION ACCOUNTANT IN PRINT ARTS OFFSET PRINTING , OF THE PROVINCE OF SANTO DOMINGO Tsáchilas JANUARY TO MARCH OF 2013 " , was developed with the aim of improving economic control company and hence for maximum optimization of resources to enable the enlargement of the company. Also, learn effectively an economic situation that will provide financial statements for your landlord to take the right decisions. The objectives were met in full, it was designed main and auxiliary records commensurate with the activity carried out in the press, and the plan was manual and accounts that are used in the printing and this applied to records control of the three cost elements as raw materials, labor and manufacturing overhead costs, with grounds developed the accounting process from the initial inventory until the financial statements. It was important to each of the findings and recommendations mainly the treatment and control of the three elements of cost: raw material, labor and manufacturing overhead costs primarily because the latter is regarded as an expense and directly affects the determining the unit cost, and total processed products, reason enough for the owner to consider implementing this system cost and financial control in your company.